Fabrication and Evaluation of a Linear Fiber Optic Data Link Possessing Autoranging Capablities - Look, Christopher (My University, 1980)
The design and fabrication of a low cost optical communications link is described. The evaluation of this system shows that it can transmit bipolar analog signals in a bandwidth of O to 17 kHz with less than 0.1% non-linearity, Combined with an autoranging capability, the linear link is demonstrated to be useful for high accuracy remote data acquisiton.
Part A of two parts. Part B titled: "The Processing and Evaluation of Long Lived GaA1As Channeled Substrate Planar Lasers".
Keywords: fabrication; linear fiber optic; autoranging; data link